2013
DOI: 10.1016/j.ridd.2013.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Using ABC narrative recording to identify the function of problem behavior: A pilot study

Abstract: Many professionals report using ABC narrative recording to identify the function of problem behavior in children with developmental disabilities, but research has not established whether their analyses yield valid results. Thus, the purpose of this study was to examine whether the function identified by expert reviewers using ABC narrative recordings would match the one identified by a functional analysis (FA) and the Questions About Behavioral Function (QABF) scale in four children with developmental disabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
5
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 43 publications
1
23
5
4
Order By: Relevance
“…The second and fourth authors conducted a narrative descriptive assessment (e.g., see Luna, Nadratu, Palmier, Brestan-Knight, & Rapp, 2018) of Aubrey’s behavior in the presence of her family during a 2-hr session in Aubrey’s home. Lanovaz, Argumedes, Roy, Duquette, and Watkins (2013) showed that experts (i.e., BCBAs) could use the results of Antecedent-Behavior-Consequence (ABC) narratives to identify the correct function of problem behavior. Results of the descriptive assessment, as well as results from prior evaluations, suggested that Aubrey’s vocalizing was maintained by attention from her sister and parents.…”
Section: Methodsmentioning
confidence: 99%
“…The second and fourth authors conducted a narrative descriptive assessment (e.g., see Luna, Nadratu, Palmier, Brestan-Knight, & Rapp, 2018) of Aubrey’s behavior in the presence of her family during a 2-hr session in Aubrey’s home. Lanovaz, Argumedes, Roy, Duquette, and Watkins (2013) showed that experts (i.e., BCBAs) could use the results of Antecedent-Behavior-Consequence (ABC) narratives to identify the correct function of problem behavior. Results of the descriptive assessment, as well as results from prior evaluations, suggested that Aubrey’s vocalizing was maintained by attention from her sister and parents.…”
Section: Methodsmentioning
confidence: 99%
“…A recent review of the QABF showed that it is currently the most research-supported indirect behavioral assessment (Matson, Tureck, & Rieske, 2012). In particular, several very recent studies have demonstrated high convergence between QABF scores and experimental analysis data, especially when the behaviors are maintained by automatic reinforcement (e.g., Lanovaz, Argumedes, Roy, Duquette, & Watkins, 2013; Watkins & Rapp, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, a single study has examined the concurrent validity of ABC narrative recording to identify the function of challenging behavior. Lanovaz et al (2013) reported that expert-reviewers using ABC narrative recording identified the same function as functional analyses in 75% of cases. That said, Lanovaz et al (2013) has not been replicated and the authors used only 12 expert-reviewers, which limits the generality of their findings.…”
Section: Functional Assessment Interviewsmentioning
confidence: 99%